Single Language, Code Switching, and Code Mixing in the Banjar-Dayak Bilingual Society Family in Palangka Raya (Universitas Negeri Semarang, 2019)
This research is motivated by the diversity of languages ​​used by the Banjar-Dayak speech community in the City of Palangka Raya, which represents the existence of bilingual and multilingual communities with conditions such as these that lead to the choice of languages ​​used by the community, especially in the domain of the family. This purpose of the study was to describe the form of language choices used in the family domain. Data collected using the listening method and proficient method. Analysis of the data in this study used a translational equivalent using the Pilah Determinant (PUP) technique and an advanced technique consisting of two techniques, namely the Linking Appeal Equalization technique (HBS) and the Differential Linking Technique (HBB). The results showed that the language form of the bilingual community of Banjar-Dayak was in the form of a single language including Dayak and Banjar languages, code-switching, and code-mixing.